The Influence of Organizational Culture on Employee Performance with Organizational Commitment as Mediation Variable - Selvia Ilmiatun Muvida; Uci Yuliati; Sandra Irawati (Universitas Muhammadiyah Malang, 2023)
The purpose of this research is to analyze the effect of organizational culture on employee performance mediated by organizational commitment. This research was conducted on employees of PT. BPRS Bhakti Sumekar Sumenep with a total of 58 respondents. The sampling technique uses the total sampling technique. Data collection was carried out using a questionnaire technique. The data analysis technique uses path analysis and the SPSS 25 program. The results of this study indicate that organizational culture shows strong results, organizational commitment shows high results and employee performance shows high results. There is a significant influence between organizational culture influencing employee performance, organizational culture influencing organizational commitment, organizational commitment influencing employee performance, and organizational commitment mediating the influence of organizational culture on employee performance, meaning that increasing organizational commitment can increase the influence of organizational culture on employee performance.